Spontaneous nystagmus with an upbeat component: Central or peripheral vestibular disorders? - Ling, Xia; Wu, Yue-Xia; Feng, Yu-Fei; Zhao, Tong-Tong; Zhao, Gui-Ping; Kim, Ji-Soo; Yang, Xu; Wang, Zhao-Xia (Frontiers in Neurology, 2023)
Abstract Objective: To determine the etiologies of spontaneous nystagmus (SN) with an upbeat component. Methods: We retrospectively recruited 43 patients with SN with an upbeat component at a university hospital in China from 2020 to 2022. We analyzed their clinical and neurotologic findings and the final diagnosis. Results: Peripheral vestibular disorders were diagnosed in 21 (48.8%) patients, central in 21 (48.8%), and undetermined in one (2.3%) patient. Fifteen (34.9%) of them showed pure upbeat nystagmus (UBN), while 28 (65.1%) exhibited SN mixed with an upbeat component, mixed upbeat-horizontal in 15, mixed upbeat-horizontal-torsional in 12, and upbeat-torsional in the remaining one. Pure UBN and mixed SN with the upbeat component no less than the horizontal component were more common in central than in peripheral vestibular disorders [17 (81.0%) vs. 8 (38.1%), Chi-Square test, p = 0.011). The underlying causes mostly included acute unilateral peripheral vestibulopathy (n=11), posterior circulation infarction (n = 9), benign recurrent vertigo (n = 4), recurrent vertigo with positive antiphospholipid antibodies (n = 3), vestibular migraine (VM, n = 3), and VM of childhood (n = 2). Conclusion: SN with an upbeat component can be seen in both central and peripheral vestibular disorders. Central vestibular disorders should be suspected when patients show pure UBN or mixed SN with the upbeat component no less than the horizontal one. Key words: upbeat nystagmus, etiology, posterior circulation infarction, acute unilateral vestibulopathy